Edukasi Nilai-Nilai Ekonomi Syariah melalui Konten Digital bagi Anak-Anak: Education on Sharia Economic Values through Digital Content for Children - Annisa, Nur; Rozikin, Achmad Zainul; Suniati, Suniati (Anterior Jurnal, 2025)
Education related to Sharia economics plays an important role in helping understand economic values based on Islamic religious teachings, especially among children. The rapid development of digital technology currently impacts the adjustment of educational facilities, one of which is through digital content. Digital media-based educational content is increasingly considered an effective means of teaching sharia economic values to children. This research aims to describe the potential and benefits of education on Sharia economic values through digital content, especially animated videos on the YouTube platform. This research uses literature study and content analysis methods to identify various types of existing digital content and evaluate their effectiveness in transferring Sharia economic values. The object used in this research is an animated video produced by Bank Indonesia. The research results show that digital content can provide children with a better and more enjoyable understanding of Sharia economics. Apart from that, the research results show that there are Sharia economic values and principles that are taught through digital content such as halal food and the prohibition of usury. In addition, through digital content, the message is conveyed in an interesting and easy-to-understand way.